2006
DOI: 10.1038/sj.ki.5001632
|View full text |Cite
|
Sign up to set email alerts
|

ADMA, proteinuria, and insulin resistance in non-diabetic stage I chronic kidney disease

Abstract: The rationale of this study is based on the fact that, both proteinuria and elevated asymmetric dimethyl arginine (ADMA) levels have been linked to the progression of vascular disease. Currently, there is not enough knowledge about any association between the levels of proteinuria and ADMA levels. Seventy-eight non-diabetic patients (42 men, 36 women, mean age of 26.1+/-5.2 years) with proteinuria having normal glomerular filtration rate were enrolled along with 38 healthy subjects (20 men, 18 women, mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 48 publications
5
79
1
6
Order By: Relevance
“…Both dialysis-related and dialysis-independent factors may promote inflammation by stimulating the synthesis and/or release of several pro-inflammatory cytokines like CRP, IL-1, IL-6, TNF-␣, and IFN-␥ (23). Impaired endothelium-dependent vasodilation is a hallmark in patients with ESRD (31), and high ADMA levels are considered as a major factor in endothelial dysfunction in chronic renal failure (31,32). In our study, the majority of ESRD patients had circulating levels of ADMA and CRP above the corresponding upper limit of the normal range (59% and 55%, respectively).…”
Section: Inflammation and Endothelial Dysfunction In Esrd Patientsmentioning
confidence: 73%
“…Both dialysis-related and dialysis-independent factors may promote inflammation by stimulating the synthesis and/or release of several pro-inflammatory cytokines like CRP, IL-1, IL-6, TNF-␣, and IFN-␥ (23). Impaired endothelium-dependent vasodilation is a hallmark in patients with ESRD (31), and high ADMA levels are considered as a major factor in endothelial dysfunction in chronic renal failure (31,32). In our study, the majority of ESRD patients had circulating levels of ADMA and CRP above the corresponding upper limit of the normal range (59% and 55%, respectively).…”
Section: Inflammation and Endothelial Dysfunction In Esrd Patientsmentioning
confidence: 73%
“…14,15 Because the kidneys provide a significant route for clearance of methylarginines, 16,17 it is perhaps not surprising that ADMA 18 and SDMA concentrations increase in CKD patients even without proteinuria, 19,20 or that proteinuria with reduced renal function is associated with both elevated ADMA and endothelial dysfunction. 10,21,22 However, the patients in our study all had a nearly normal renal function. Inflammation, defined here as an elevated serum hsCRP, is also known to influence ADMA and has been proposed to be one factor linking ADMA to CVD.…”
Section: Discussionmentioning
confidence: 88%
“…9 We recently reported that nondiabetic proteinuria is associated with elevation of ADMA in CKD. 10 In this study, we hypothesized that this might be the result of an abnormal protein turnover in proteinuria, which might be further exacerbated in SA. We furthermore hypothesized that an ADMA-associated endothelial dysfunction would be yet another factor linking proteinuric CKD to an increase in cardiovascular risk.…”
mentioning
confidence: 99%
“…Recently, it has been reported that the patients with proteinuria have higher ADMA levels along with impaired insulin sensitivity (35). Increased ADMA appears to be a potential link between proteinuria and endothelial dysfunction and atherosclerotic complications.…”
Section: Discussionmentioning
confidence: 99%